PENGEMBANGAN DESA WISATA PESONA WANAJAYA BERBASIS PARTISIPASI MASYARAKAT - Putri Barinda Shofiana; Muhtadi Muhtadi (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2023)
This research is a study related to the development of tourist villages through Wanajaya community participation. This study aims to determine the forms of participation, the ladder of participation, and the supporting and inhibiting factors in the process of forming and developing the Wanajaya Enchantment Tourism Village. Starting from hobbyists who love motocross and bicycles, a tourist village was established which became a place to channel various types of hobbies while being able to recreate. The formation of a tourism awareness group (POKDARWIS) makes the tourist village have a managerial system in managing all the interests that exist in the activity program. Various types of playgrounds and facilities are an attraction for visitors. Pesona Wanajaya Tourism Village has experienced significant development with the age of its establishment which has only been three years old, but has received achievements in the national competition. In this study the authors used qualitative research methods, with data collection techniques through interviews, observation, and documentation. The research here reveals a situation or condition as it is based on observations made directly. The results of this study are the existence of community participation in the form of ideas / thoughts, energy, thoughts and energy, expertise, and goods; Then the ladder of community participation is at the level of placation and partnership, then there are things that become supporting factors and inhibiting factors in the process of forming and developing the Wanajaya Pesona Tourism Village, Cibitung District, Bekasi Regency.